Analysis of the third‐ and fourth‐generation cephalosporin use for the treatment of infections caused by Gram‐negative bacteria in hospital settings. Issue 12 (December 2016) - Protic, Dragana; Pejovic, Aleksa; Djukanovic, Nina; Toskovic, Borislav; Zdravkovic, Marija; Todorovic, Zoran
Summary: Objective: The aims of our study were to assess the prevalence and distribution of Gram‐negative (G‐) bacteria in hospital isolates, their sensitivity to the third‐ and fourth‐generation cephalosporins (c3 and c4), therapeutic use of c3 and c4 in the treatment of G‐ infections and drug utilisation data. Research design and methods: This cross‐sectional study collected medical records data from the General Hospital "Gornji Milanovac" (GM) and the University Medical Center "Bezanijska kosa" (BK). The time frame of the study was 12 months. Microbiological and clinical parameters, and c3/c4 drug utilisation were analysed. Results: Escherichia coli were the most predominant pathogen in GM and BK, accounting for 43% and 28% of all G‐ isolates, respectively (GM), 884 G‐ isolates obtained from 606 patients; BK, 1766 isolates obtained from 1045 patients). Nearly half of the isolates (55% and 43%) were obtained from urine samples collected from the surgical ward (GM), and the internal medicine wards and intensive care unit (BK). On average, the resistance rate of G‐ strains against c3 and c4 reached 40% and 70%, respectively (lowest in E. coli, 8%‐25%; highest in Acinetobacer baumannii, 67%‐100%). Resistance rate of Pseudomonas spp. to cefepime and ceftazidime was low/moderate (0%‐30% and 19%‐47%). In BK, the adult patients were older than in GM (75 vs 66 years), with longer hospital stay (19 vs 10 days) and bacteria were isolated later during hospitalisation (10 vs 2 days). C3 and c4 were more often used in empirical therapy (83% vs 64%) in BK. Ceftazidime and cefepime were used more often in BK than in GM (2.036 vs 69 DDD/y and 586 vs. 126 DDD/y, respectively). Conclusion: The use of c3 and c4 in the treatment of G‐ infections in both hospitals should be re‐evaluated in accordance with current guidelines and local resistance.